Clinical Outcomes of Scleral Buckling combined with Vitrectomy Pars Plana for Rhegmatogenous Retinal Detachment: Oral Presentation - Observational Study - Resident - Andry Lukandy; Sumanti, Eugeni (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives The various types of primary interventions for rhegmatogenous retinal detachment (RRD) include pars plana vitrectomy (PPV), scleral buckling (SB), and combination of both. Intraocular tamponade with silicone oil (SO) or expanding gas. This research was conducted to evaluate the clinical outcomes of SB combined with PPV as a treatment for RRD. Methods This research was prospective descriptive study with total sampling for RRD treated by SB combined with PPV from August 2022 to January 2023 in RSUP. Prof. Dr. R.D. Kandou. We observed the BCVA, IOP before and after the surgeries. Clinical findings, intraocular tamponade and complications after the surgeries were observed. Results Most of the patients was male with average age of 28 ± 40 years. RRD was observed in 6 eyes and laterality on right eye. BCVA was 2.5 ± 2 logMAR before the surgery and 2.3 ± 1 logMAR 1 month after the surgery. Preoperative IOP was 7 ± 11 mmHg and 13.6 ± 10 mmHg 1 month after the surgery. Macular detachment, 1 Quadrant Detachment, 1 Number of retina break mostly on superotemporal quadrant were found the most. Proliferative vitreoretinopathy was found in 1 eye. Intraoperative triamcinolone used in 4 eyes and perfluorocarbon in 1 eyes. Subconjunctival bleeding was found the most, followed by corneal edema and subretinal hemorrhage as postoperative complications respectively. Conclusion There were several clinical condition seen such as BCVA after the surgery that didn’t improve as expected, High IOP found in several eyes and subconjunctival bleeding was the complication found the most in these eyes.